Strategic leadership 5.0 practices among principals in Jordan - AL-OMARI, AIEMAN (Journal of Interdisciplinary Studies in Education, 2026)
This study addresses the gap in empirical research on Strategic Leadership 5.0 implementation in developing nations, with specific focus on Jordan. The research examined: (1) current adoption levels of Strategic Leadership 5.0 dimensions among Jordanian principals, (2) implementation challenges, and (3) strategies for effective integration. Using a mixed-methods approach, data were collected from 300 teachers via surveys including both quantitative scales and open-ended questions. Results indicated moderate adoption across all dimensions (M=2.93-3.04), with significant differences based on teacher sex and experience. Key challenges included insufficient training, resistance to change, and resource limitations. The study recommends comprehensive professional development, policy alignment, and infrastructure investment to enhance Strategic Leadership 5.0 implementation in Jordanian schools.